INTERCULTURAL COMMUNICATION IN AL-QUR’AN (COMPARATIVE STUDY OF AL-QURTHUBI AND IBN KATHIR INTERPRETATION IN SURAH AL-IMRAN: 103) - Fitriani, Elsyi; Mahadika, Alam (Universitas Islam Negeri Mataram, 2024)
The research focus on the comparison of the interpretation of Al-Qurthubi and Ibn Kathir on surah Al-Imran: 103. This research uses literature study method and comparative method. The findings of the research are that Tafsir Al-Qurthubi looks at the legal and fiqh aspects, while Ibn Kathir focuses on normative or historical approaches, such as taking the story of Aus and Khazraj, to illustrate the importance of unity. It can be said that the context of intercultural communication in Islam has values that are collective, unity, and obedience to the guidelines of Allah's religious rope to avoid the people being divided due to conflict and division.